Catalyzing role of erythropoietin on the nitric oxide central pathway during the ventilatory responses to hypoxia. Issue 2 (14th February 2014) - Voituron, Nicolas; Jeton, Florine; Cholley, Yannick; Hasnaoui‐Saadani, Raja El; Marchant, Dominique; Quidu, Patricia; Favret, Fabrice; Richalet, Jean‐Paul; Pichon, Aurélien
Abstract The N‐Methyl‐d‐Aspartate (NMDA) receptors – neuronal nitric oxide synthase (nNOS) pathway is involved in the ventilatory response to hypoxia. The objective was to assess the possible effect of erythropoietin deficiency and chronic exposure to hypoxia on this pathway during ventilatory response to acute hypoxia. Wild‐type (WT) and erythropoietin‐deficient (Epo‐TAgh) male mice were exposed (14 days) either to hypobaric hypoxia (Pb = 435 mmHg) or to normoxia. The ventilation was measured at 21% or 8% O2 after injection of vehicle (NaCl), nNOS inhibitor (SMTC) or NMDA receptor antagonist (MK‐801). Nitric oxide production and the expression of NMDA receptor and nNOS were assessed by real‐time RT‐PCR and Western blot analyses in the medulla. At rest, Epo‐TAgh mice displayed normal ventilatory parameters at 21% O2 but did not respond to acute hypoxia despite a larger expression of NMDA receptors and nNOS in the medulla. Ventilatory acclimatization to hypoxia was observed in WT but was absent in Epo‐TAgh mice. nNOS inhibition blunted the hypoxic ventilatory acclimatization of WT mice without any effect in Epo‐TAgh mice. Acute hypoxic ventilatory response (HVR) was increased after chronic hypoxia in WT but remained unchanged in Epo‐TAgh mice. Ventilatory response to acute hypoxia was modified by MK‐801 injection in WT and Epo‐TAgh mice. The results confirm that adequate erythropoietin level is necessary to obtain an appropriate HVR and a significant ventilatory acclimatization to hypoxia. Furthermore, erythropoietin plays a potential catalyzing role in the NMDA‐NO central pathway during the ventilatory response and acclimatization to hypoxia.